انعكاسات التأثيرات البيئية لأنشطة الوحدات الاقتصادية على عمل مراقب الحسابات بالتطبيقق على عينة مختارة من الوحدات الاقتصادية - منهل مجيد أحمد العلي (PROSPECTIVE RESEARCHES, 2023)
The present research tackles the credible information which gives details on the pollution due to the activities of the economic units. The effects of pollution are represented by gases, polluted water and air, radiation, industrial waters, vibrations, and trash. Management of units must establish environment system and periodically check environmental activities using neutral accountants or any other official side appointed by regulations environment protection. The effects of those activities should be checked to show their impact en the employees, workers, the environment, and the accountants during their work in such units. Their should be reviewed and considered to esstimate the effect of pollution on their health whend doing their job.